Mandatory fun, creating community participation - Regan, Jeannie (2025)
My practice is grounded in problem solving, and inventing new opportunities for people to engage with the arts in public spaces. I make art to contribute to the growth of empathetic, optimistic and resilient communities. I start new work by identifying an issue in the community and devising a creative solution. The goal is for the work to be a combination of kind, clever and elegant. At times the art is in the idea itself, and other times it is in the act of moving units of energy towards a common good. Logistics, strategy and administration are foundational parts of my practice. Instead of sketchbooks I have spreadsheets, in place of materials explorations I send emails, compose text messages and book meeting spaces. The most elusive criteria is humor. “Yes, but is it funny?” is a recurring concern. Maintaining humor and elegance while still honoring the gravity of the problem is where the cleverness is tested. Creating a sense of fun and eliciting joy are critical components, the necessary counterspell against the obstacles that my work seeks to overcome. In this thesis I will be describing my practice and placing it within the context of contemporary social practice. I will also reference influential artists and writers; Corita Kent, Es Devlin and Rebecca Solnit.